Bactericidal Activity of the Bacterial ATP Synthase Inhibitor Tomatidine and the Combination of Tomatidine and Aminoglycoside Against Persistent and Virulent Forms of Staphylococcus aureus - Langlois, Jean-Philippe; Millette, Guillaume; Guay, Isabelle; Dubé-Duquette, Alexis; Chamberland, Suzanne; Jacques, Pierre-Étienne; Rodrigue, Sébastien; Bouarab, Kamal; Marsault, Éric; Malouin, François (Frontiers in Microbiology, 2020)
Tomatidine (TO), a steroid alkaloid, exerts a strong bactericidal activity on the infection-persistent phenotype of Staphylococcus aureus, the small-colony variant (SCV), with a minimal inhibitory concentration (MIC) of 0.06 μg/ml. Also, the combination of TO to an aminoglycoside (AMG) shows a strong synergistic effect against prototypical (WT) S. aureus (MIC 0.06 μg/ml), which is otherwise unaffected by TO alone (MIC >128 μg/ml). We have recently established that the ATP synthase (subunit AtpE) was the molecular target of TO and that TO reduces the production of ATP in S. aureus. The purpose of this study was to understand how TO and the TO-AMG combination exert bactericidal activities against S. aureus SCV and WT strains, respectively. The impact of TO and of the TO-gentamicin (GEN) combination on the membrane potential and generation of reactive oxygen species (ROS) were determined using florescent probes. GEN uptake in WT was assessed in the presence of TO. Virulence of SCV and WT strains as well as of in vitro-selected mutants showing resistance to TO or the TO-GEN combination was evaluated in a murine thigh infection model. TO causes a reduction in membrane potential in both WT and SCV, but significant amounts of ROS are only produced in SCVs. Besides, the presence of TO improves the uptake of GEN by the WT strain and the combination TO-GEN generated 2.5 folds more ROS in WT, compared to that induced by GEN alone. Under anaerobic conditions, WT adopts a fermentative slow-growth phenotype and becomes susceptible to TO even if used alone. In vivo, TO- or TO-GEN-resistant strains were significantly altered in their ability to colonize tissues. These results shed light on the mechanism of action of TO and its synergy with AMGs against S. aureus WT. TO bactericidal activity against SCVs is attributable to both a critical drop in the membrane potential accompanied by a substantial ROS production. In the WT, TO helps GEN uptake and ROS is also important for the synergy. Acquiring resistance to TO significantly impairs virulence. The residual ATP synthase activity of SCVs might represent the Achilles’ heel of persistent S. aureus.